The Spatial Development Strategy and National Security Priorities of the Russian Federation - Bukhvald, Evgeniy Moiseevich; Kolchugina, Anastasiya Vladimirovna (Economy of Regions, 2019)
The analysis of the Russian strategic planning documents has demonstrated that the strategizing of spatial development is the issue, which causes the greatest difficulties both in terms of methodology and scope. The officially adopted “Strategy of the spatial development of the Russian Federation until 2025“ defines some of the main goals of the state regional policy, but fails to incorporate many important issues. Taking into account the statutory provisions on the Strategy's sources, the article aims to determine the completeness and consistency of the Strategy's initially set priorities. In particular, these priorities include the requirements of the national economic security. The main conclusions relate to the degree of the Strategy's compliance with both traditional and new tasks of the state policy of regional development. We underline achieving the positive economic equalization of the Russian Federation subjects as a traditional task of regional development policy, which directly meets the requirements of the national security. We have emphasized that the Strategy of various lacks the treatment of the aspects of institutional and economic support for implementing this strategic document's goals. One of the main conclusions highlights the need to integrate a wide range of issues concerning the development of the federal relations' economic and legal foundations into the Strategy. The effective federal relations are one of the conditions for ensuring the Russian states stability and security. In this regard, the articles conclusions rationalize the need to elaborate the next steps in both strategic planning and federal reforming in the Russian Federation. The study's results can be used for the further work on the Strategy of spatial development and development of the measures, aimed at improving the federal relations' economic and legal foundations in the Russian Federation.